2022
DOI: 10.1007/s00415-022-10969-4
|View full text |Cite
|
Sign up to set email alerts
|

Personalizing decision-making for persons with Parkinson’s disease: where do we stand and what to improve?

Abstract: Background The large variety in symptoms and treatment effects across different persons with Parkinson’s disease (PD) warrants a personalized approach, ensuring that the best decision is made for each individual. We aimed to further clarify this process of personalized decision-making, from the perspective of medical professionals. Methods We audio-taped 52 consultations with PD patients and their neurologist or PD nurse-specialist, in 6 outpatient clinics… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…The complex process of understanding each individual’s unique day-to-day functional experience is crucial for implementing interventions based on person-centered goal setting and improving physical and emotional well-being 46 , 47 . However, in their comprehensive review, Oedekoven and colleagues 48 concluded that despite evidence for the possible benefits of SCD for early identification of PD-MCI, no consensus exists for SCD research or clinical criteria.…”
Section: Discussionmentioning
confidence: 99%
“…The complex process of understanding each individual’s unique day-to-day functional experience is crucial for implementing interventions based on person-centered goal setting and improving physical and emotional well-being 46 , 47 . However, in their comprehensive review, Oedekoven and colleagues 48 concluded that despite evidence for the possible benefits of SCD for early identification of PD-MCI, no consensus exists for SCD research or clinical criteria.…”
Section: Discussionmentioning
confidence: 99%
“…Empirical studies suggest that young adults are vulnerable to negative distress and other psychological problems. Their stress mainly comes from heavy academic pressure, severe employment difficulties [3], emotional regulation [4] and COVID-19 lockdown measures [5]. As many students fail to properly cope with their stress, they start to feel helpless and develop negative expectations for their future, leading to psychological disorders or other diseases.…”
Section: Introductionmentioning
confidence: 99%